Atividade alelopática de gengibre e funcho sobre germinação e desenvolvimento inicial de plantas daninhas - Defaveri, Alexandre (2018)
The allelopathic substances are provided with the secondary metabolism of plants and have as main functions the reduction of the growth of the recipient plants, or even inhibition of the germination of the seeds. Among these species we have fennel, whose allelopathic potential on some plants is already known, and ginger that has a high antifungal potential, however, still little studied as to its allelopathic potential. Weeds are those that occur spontaneously in areas of cultivated plants, which are currently combated with the aid of chemical control. However, in order to reduce the damages in nature, the need to search for alternative methods has arisen, such as the use of the allelopathic potential of some plants on host plants, but it is known that some variables can directly influence the effect of the extract, such as the infusion time and the concentration used. The objective of this work was to evaluate the strains of ginger (Z. officinalis) and fennel (F. vulgare) on the plants receiving turnip (Raphanus raphanistrum), ryegrass (Lolium multiflorum) and black pickle (Bidens pilosa) in different concentrations. The work was carried out in 2017 at the Seeds Laboratory, Federal Technological University of Paraná, Câmpus Dois Vizinhos, Paraná, Brazil. Using turnip, ryegrass and black pickled seeds collected in the experimental area of the University. For the preparation of extracts of fennel and ginger, these were initially collected fresh, macerated and infused in the proportions of 200 g of fennel or ginger in 1000 ml of distilled water, which remained during the periods of 30 minutes, 24 and 48 hours in infusion. For the application of the extracts on the seeds of the tested species these were diluted in concentrations of 0%; 1.25%; 2.5%; 5% and 10% in distilled water. The experimental design was completely randomized, for each species to be tested, in a 2 x 3 x 5 factorial scheme (Extract Type x Infusion Period x Concentration of the extract), with four replications. For the germination tests were 36 seeds per experimental unit in gerbox boxes on equidistant paper, applying 6 ml of the extracts of the species tested, with the aid of a syringe, according to the period of infusion and concentration previously mentioned, in each gerbox. After these were closed with the cap and placed in a BOD-type chamber at 25°C, with a photoperiod of 12 hours light/dark and with a relative humidity of 80%. At the end of the experiment, the aerial and root portion of 5 seedlings per experimental unit was measured, and the fresh and dry mass, shoot and root mass were determined. According to the results it can be concluded that the extract of fennel presented better results of reduction and even inhibition of the analyzed variables in all the species of weeds under study, so that the increase of the concentrations resulted in their reduction.